Spatial and temporal distribution of rainfall and temperature in Macedonia, Greece, over a thirty year period, using GIS - Grimpylakos, G.; Karacostas, T. S.; Albanakis, K. (Bulletin of the Geological Society of Greece, 2013)
Due to increased demand and use of water resources, the European Union has established the (WFD) Water Framework Directive 2000/60 for Community action in the field of water policy. In order to achieve better water protection and management, Member States must identify and analyse European waters, on the basis of individual river basin and district. Precipitation and air temperature are directly related and at the same way interacted to the hydrological cycle and therefore with water resources. The objective on this study is to present the spatial and temporal distribution of precipitation and air temperature in Macedonia, by using GIS software (ArcMap 9.3). The data used were retrieved from 82 different meteorological stations, which belong to the Ministry of Rural Development and Food, and correspond to the thirty year period (1974-2004); all stations provided continuous daily data of precipitation while 43 of them provided also daily data of temperature. The annual temperature range and the annual total precipitation amount were calculated, at each individual station, for the thirty years of the examined period. By using GIS software and triangular interpolation scheme, the thematic maps of Macedonia for the aforementioned parameters and thermal continentality K were created. Furthermore, possible mean annual evapotranspiration for each meteorological station was estimated by Turc, Coutagne and Thornthwaite algorithms.